Analisis Pengelolaan Agroforestry dan Kontribusinya terhadap Perekonomian Masyarakat - Syaiful Bahri Zega; Agus Purwoko; Tri Martial (Peronema Forestry Science Journal, 2013)
Agroforestry is a form of community forestry. Agroforestry management related to the optimization of land use for their daily livesof farmers and in order to conserve natural resources. This study aimed to determine the contribution of agroforestry  for house hold incomes in Sitaratoit and Lobulayan Village, Tapanuli Selatan District. The results showed that total community income was Rp. 875.900.000,- per year with details incomes from agroforestry was Rp. 597.000.000,- and income from the outside the utilization of agroforestry products contributed Rp.300.900.000,-. Contribution of agroforestry products for people's income is 63% of total income. Income community outside ofagroforestry such as farmer, trader, public civil servant, pensioner and entrepreneur contribute 37% of total income. This means that agroforestry contributed greatly to the house hold income. Key words: Agroforestry, Community Income, Contribution of Agroforestry